2019
DOI: 10.1111/jch.13705
|View full text |Cite
|
Sign up to set email alerts
|

The impact of diabetes mellitus and hypertension on clinical outcomes in a population of Iranian patients who underwent percutaneous coronary intervention: A retrospective cohort study

Abstract: There are heterogeneous data regarding the impact of diabetes mellitus (DM) and hypertension (HTN) on clinical outcomes after percutaneous coronary intervention (PCI). This study explored the effect of history of DM (hDM) and HTN (hHTN), separately and in combination with each other, on major adverse cardiac events (MACE) in short‐, mid‐, and long‐term intervals after PCI. Between 2000 and 2017, 1799 patients who had PCI were registered. They were categorized in four different groups: hDM, hHTN, hDM + hHTN, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…BP-SES and DP-EES were compared in diabetic patients, and results concluded that BP stents were associated with more TLR than DP stents in diabetic people ( Kakizaki et al, 2020 ). The percentage of MACE was more in DM and hypertensive patients at a follow-up of 66.5 months, and the combined effect of DM and HTN increased the incidence of MACEs further ( Zibaeenezhad et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BP-SES and DP-EES were compared in diabetic patients, and results concluded that BP stents were associated with more TLR than DP stents in diabetic people ( Kakizaki et al, 2020 ). The percentage of MACE was more in DM and hypertensive patients at a follow-up of 66.5 months, and the combined effect of DM and HTN increased the incidence of MACEs further ( Zibaeenezhad et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study consisted of two phases: a retrospective phase (in which data were retrieved from the hospital record) and a prospective phase (follow-up of patients at 1 year duration, post-PCI). The major adverse cardiovascular events are defined as the composite endpoints of non-fatal MI, stent thrombosis, clinically driven TVR/TLR, and cardiovascular death ( Zibaeenezhad et al, 2019 ). The XIENCE Xpedition Everolimus-Eluting Stent (EES) having a cobalt chromium strut loaded with 100 µg/cm 2 everolimus and XIENCE Prime (Abbott) is also a 100 µg/cm 2 everolimus-coated stent ( Abbott, 2013 ; Abbott, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who had fasting plasma glucose of ≥126 mg/dL (7.0 mmol/L) or 2 h plasma glucose of ≥200 mg/ dL (11.1 mmol/L) during oral glucose tolerance test or A1C of ≥6.5% (48 mmol/mol) or with classic symptoms of hyperglycemia or hyperglycemic crisis, a random plasma glucose of ≥200 mg/dL (11.1 mmol/L), or receiving antihyperglycemic medications before index PCI were considered as having diabetes mellitus (DM). Patients who had systolic blood pressure of ≥130 mmHg or diastolic blood pressure of ≥80 mmHg or both or receiving antihypertensive medications before index PCI were considered as having hypertension (HTN) [9].…”
Section: Methodsmentioning
confidence: 99%
“…14 Diabetes mellitus, as a risk factor for HTN, causes significantly worse major adverse cardiac events following percutaneous coronary intervention. 15 16 …”
Section: Introductionmentioning
confidence: 99%